2015
DOI: 10.1002/eji.201445218
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3 enzymes restrict marginal zone B cells

Abstract: In general, a long-lasting immune response to viruses is achieved when they are infectious and replication-competent. In the mouse, the neutralizing antibody response to Friend murine leukemia virus is contributed by an allelic form of the enzyme Apobec3 (abbreviated A3). This is counterintuitive, because A3 directly controls viremia before the onset of adaptive anti-viral immune responses. It suggests that A3 also affects the antibody response directly. Here we studied the relative size of cell populations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…These data are in line with reports showing that beyond their ability to directly act on viral genomes, APOBEC-induced deamination can positively modulate immunological response. [45][46][47] The role of the two APOBEC-related MutSigs 2 and 13 was cancer type specific: For example, while we detected many significant associations with both MutSigs in BRCA, much stronger associations were detected for MutSig 2 compared to MutSig 13 in CESC. Similar observations were made for cancers harboring mutational signatures associated with DNA repair deficiency including MSI and POLE-mutations where specific immune cell compositions e1526613-10 were associated with each of these deficient repair pathways in a cancer-type specific manner.…”
Section: Discussionmentioning
confidence: 79%
“…These data are in line with reports showing that beyond their ability to directly act on viral genomes, APOBEC-induced deamination can positively modulate immunological response. [45][46][47] The role of the two APOBEC-related MutSigs 2 and 13 was cancer type specific: For example, while we detected many significant associations with both MutSigs in BRCA, much stronger associations were detected for MutSig 2 compared to MutSig 13 in CESC. Similar observations were made for cancers harboring mutational signatures associated with DNA repair deficiency including MSI and POLE-mutations where specific immune cell compositions e1526613-10 were associated with each of these deficient repair pathways in a cancer-type specific manner.…”
Section: Discussionmentioning
confidence: 79%
“…Previous study designed to identify a host cell suppressor of the HIV-1 accessory protein, viral infectivity factor (VIF), reported its function as an antiviral host factor [ 19 , 34 ]. A3G has also been shown to promote CD8+ cytotoxic T lymphocytes (CTL) recognition of infected T lymphatic cells and restrict marginal zone B cells, possibly resulting in a shift from a prompt immune response to a much more sustained germinal center B cell response [ 35 ]. Recent studies have shown that A3A induced by inflammation-related factors edits the mRNAs of thousands of genes, some associated with viral pathogenesis in macrophages and monocytes [ 36 , 37 ].…”
Section: The Biological Function Of the Apobec Familymentioning
confidence: 99%
“…Curiously, the St6gal1 -KO MZ B cells had a slight but distinct SNA signal of ~1000, which was ~5% of the wild-type MZ counterparts, but at least 4-fold higher than other B cell populations (Supplementary Figure 3 ). This was likely due to ST6GalNAc sialyltransferases, as reported by others, and was not explored further here ( 41 ). Cell surface expression of CD22 is shown in Figure 2C .…”
Section: Resultsmentioning
confidence: 76%